Delayed‐type hypersensitivity (DTH) test anergy does not impact CD4 reconstitution or normalization of DTH responses during antiretroviral therapy. Issue 2 (4th February 2014) - Minidis, Natascha M; Mesner, Octavio; Agan, Brian K; Okulicz, Jason F
Abstract : Introduction: Delayed‐type hypersensitivity (DTH) testing is an in vivo assessment of cell‐mediated immunity. Although highly active antiretroviral therapy (HAART) improves immunologic parameters, the relationship between DTH responsiveness and CD4 gains on HAART is not completely understood. We investigated CD4 reconstitution and the change in DTH responses from treatment baseline through 24 months of viral load (VL)‐suppressive HAART in the U.S. Military HIV Natural History Study. Methods: Treatment‐naïve subjects with VL <400 copies/mL after ≥24 months on HAART were included ( n =302). DTH testing consisted of ≥3 recall antigens, and responses were classified by the number of positive skin tests: anergic (0–1) or non‐anergic (≥2). Pre‐HAART DTH results were compared for the outcome of CD4 reconstitution at 24 months of HAART. Improvement in DTH responses was also analyzed for those anergic before HAART initiation. Results: Non‐anergic responses were observed in 216 (72%) participants, while 86 (28%) individuals were anergic prior to HAART initiation. Demographically there were similar distributions of age at HIV diagnosis and HAART initiation, as well as gender and race or ethnicity. There were no significant differences between non‐anergic and anergic participants in pre‐HAART CD4 count (409 cells/μL, interquartile range (IQR) 315–517 vs. 373 cells/μL, IQR 228–487; p =0.104) and VL (4.3 log10 copies/mL, IQR 3.4–4.9 vs. 4.4 log10 copies/mL, IQR 3.6–5.0; p =0.292). Median CD4 gains 24 months after HAART initiation were similar between the non‐anergic (220 cells/μL, IQR 115–358) and anergic groups (246 cells/μL, IQR 136–358; p =0.498). For individuals anergic before HAART initiation, DTH normalization occurred at 24 months post‐HAART in the majority of participants (51 of 86, 59%). Normalization of DTH responses was not associated with CD4 count at HAART initiation (OR 0.73, 95% CI 0.47, 1.09 per 100 cells; p =0.129) nor with AIDS diagnoses prior to HAART (OR 0.34, 95% CI 0.04, 2.51; p =0.283). Conclusions: DTH responsiveness has been shown to predict HIV disease progression independent of CD4 count in untreated individuals. In the setting of HAART, pre‐HAART anergy does not appear to impact CD4 gains or the ability to normalize DTH responses after 24 months of VL‐suppressive HAART.